The Effect of Plastic Waste Attachment on Branching Coral to Zooxanthellae Abundance in the Kelapa Dua Island Waters, Seribu Islands - Fadel Muhammad; Neviaty Putri Zamani; Meutia Samira Ismet; Muhammad Irlan Assidiq Kusuma Ramadhan (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight • Light intensity from plastic waste was positively correlated with the abundance of zooxanthellae in corals. • The abundance of zooxanthellae between sack plastic and clear plastic treatment tended to be the same. • The treatment of packaging plastic was treated with the lowest light intensity. • The treatment of black plastic was the treatment that produced the lowest abundance of zooxanthellae.